Saints of the household - Tison, Ari (Farrar Straus Giroux, 2023)
When brothers Max and Jay help a classmate in trouble, they struggle with the consequences of their violent actions and worry they may be more like their abusive father than they thought, so the brothers turn to their Bribri roots to find their way forward.